The Village of the Damned? Myths and Realities of Structured Begging Behaviour in and Around Phnom Penh. Issue 1 (2nd January 2016) - Parsons, Laurie; Lawreniuk, Sabina
Abstract: This paper concerns the nature of structured begging migration in Phnom Penh, as well as its impact and meaning in sender communities. It interrogates a popular myth known throughout Cambodia concerning the supernatural motivation of 'rich' beggars, arguing that its prevalence reflects the growing incidence of structured, circular migration based around alms seeking in the capital. In doing so, it seeks to bridge the lacuna between the literature on begging and that on migration by showing that the distinction between the two is both blurred and straddled by migrants in many cases.